Lessons learned from a gender-specific educational programme supporting young women with experience of domestic abuse. (December 2022) - Warwick-Booth, Louise; Coan, Susan
Background: Domestic abuse is a public health issue, and increasing evidence suggests that young women are more likely to suffer than older women, yet limited evidence exists in England about educational and intervention programmes for young women at risk. Study's objectives: To evaluate a gender-specific (women-only) programme aimed at educating young women aged 13–25 years about abuse and staying safe in one English city. Setting: A third sector (charitable) organisation, aiming to improve women's health in one English city delivered the programme over a 3-year period, funded by the Big Lottery Fund. Young women received both peer and one-to-one support, to educationally inform them, develop their skills and improve their capabilities in responding to abuse. Method: This qualitative evaluation captured the perspectives of young women accessing the programme ( n = 33), exploring the positive difference that it made to their lives. We also captured the views of internal stakeholders in 2018 ( n = 2), then followed up in 2020 ( n = 3), and external stakeholders referring young women to the programme ( n = 8). Results: The programme met its aims. Self-reported changes in young women's lives included increased knowledge about staying safe and being happier. Some young women gained or retained custody of their children, and others exited harmful relationships. Young women identified a range of mechanisms of success including a non-judgemental approach from workers, peer support and a trusted space in which to meet and learn. The programme increased young women's skills to stay safe while improving their mental wellbeing. Conclusion: The programme worked well for young women who accessed it. However, it could not reach all those in need, was only funded in the short-term and tended to individualise the responsibility for staying safe. Further research is needed in other community-based educational programmes to provide evidence of their effectiveness as well as transferrable models for workers in other contexts.